A comparative analysis of literary depictions of social violence in two important 16th Century autobiographies, from the perspective of the fencing manuals of the Renaissance. - Chandler Jean (Bern Open Publishing, 2015)
In the late 16th century two interesting individuals made substantial contributions to the relatively new genre of the autobiography. In 1595 Bartholomäus Sastrow (1520-1603), a north German burgher, notary, diplomat, and eventually burgomeister of the Hanseatic City of Stralsund, penned his life story. Benvenuto Cellini (1500-1571), goldsmith, soldier, musician and famous Renaissance artist from Florence, wrote his memoir between 1558 and 1563. Though they were born twenty years apart, both men had similar backgrounds. Both were from the lower-middle strata of society but rose to high status, both were widely traveled and directly acquainted with the most powerful individuals of their time (as well as some of the most lowly) and both experienced firsthand some of the most dramatic and important political and military events of the mid-16th century.